Assessment of Antioxidant and Cytotoxic Activities of Extracts of Dendrobium crepidatum - Mukti Ram Paudel; Mukesh Babu Chand; Basant Pant; Bijaya Pant (Biomolecules, 2019)
Dendrobium crepidatum is an epiphytic orchid found in south Asia including Nepal and China. This orchid species is widely used in traditional Chinese medicine (TCM) for the treatment of cancer, diabetes, cataracts, and fever. The objectives of the present research were to assess the antioxidant and cytotoxic properties of its stem’s extracts with the identification of bioactive secondary metabolites. The antioxidant and cytotoxic activities were evaluated using the DPPH (2,2-diphenyl-1-picrylhydrazyl) and MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assays, respectively, and compounds were identified using GC−MS (gas chromatography and mass spectrometry). Ethanol and acetone extracts scavenged 94.69 ± 0.10% and 93.41 ± 0.86% of DPPH free radicals, respectively. They showed 50% inhibition of DPPH free radicals (IC50) at concentrations of 73.90 µg/mL and 99.44 µg/mL, which were found to be statistically similar to that of ascorbic acid (control). Chloroform extract inhibited the growth of 81.49 ± 0.43% of HeLa (human cervical carcinoma) cells and hexane extract inhibited the growth of 76.45 ± 4.26% of U251 (human glioblastoma) cells at 800 µg/mL concentration. These extracts showed 50% inhibition of cell growth (IC50) toward both the HeLa and U251 cell lines at their high concentrations, which were found statistically significantly different from that of cisplatin drug (control). The above extracts showed antioxidant and cytotoxic properties, potentially due to the presence of tetracosane, triacontane, stigmasterol, and some phenol derivatives (2-methoxy-4-vinylphenol, 2-methoxy-5-(1-propenyl)-phenol, p-mesyloxyphenol, and 2,6-dimethoxy-4-(2-propenyl)-phenol). This study explores the potential of this orchid in alternative medicine toward the development of drugs from its medicinally active compounds.